Mechanical circulatory support in failing single-ventricle physiology - Ryan L. Kobayashi, MD; Christina J. VanderPluym, MD (JHLT Open, 2025)
The use of ventricular assist device (VAD) therapy for advanced heart failure in infants and children with single-ventricle (SV) congenital heart disease (CHD) has expanded rapidly. However, issues pertaining to patient size, developmental hemostasis, device availability, complicated anatomy, and complex modes of hemodynamic/circulatory failure associated with each stage of SV palliation make VAD support particularly challenging in this population. Over the last 20 years, there has been significant improvement in support outcomes for this complex population; however, survival and rates of adverse events still lag behind children with other diagnoses. Herein, we review current mechanical circulatory support approaches, ongoing challenges, and outcomes for patients with SV CHD.